Foreign Aid and Economic Conditionality in Africa, 1960-2010: A Historical Analysis of Complex Relations - Okoeguale, Hysaint Eiguedo; Ibukun, Eguzoro Uchechi; Emilia, Ejovi Oghenemarho (Global Journal of Cultural Studies, 2025)
This study examines the nature and patterns of foreign aid and economic conditionalities in sub-Saharan Africa from the early 1960s, when most African countries gained independence, to the early 2000s, a period that saw the rise, consolidation, and gradual transformation of economic conditionality as a central feature of aid relations. It notes that economic conditionality refers to the policy requirements, often based on neoliberal economic principles, that donor countries and multilateral institutions, such as the International Monetary Fund (IMF) and the World Bank, impose on recipient states as a precondition for accessing loans, debt relief, or development grants. The article argues that these conditions were most aggressively implemented during the 1980s and 1990s, especially through Structural Adjustment Programs (SAPs), which sought to reshape African economies by enforcing market liberalization, privatization, and fiscal austerity. The focus on sub-Saharan Africa is intentional, as this region was disproportionately targeted for policy-based lending and remains the most aid-dependent part of the continent, making it a crucial site for assessing the long-term impact of foreign aid conditionalities. This study scrutinizes the rationale behind these aid conditions by analyzing the policy objectives of donor institutions such as the IMF, the World Bank, and major Western governments, as well as the perspectives of African scholars and policymakers. The study draws on theoretical debates among dependency theorists, neoliberal economists, and postcolonial scholars, who disagree on whether conditional aid promotes sustainable development or reinforces neocolonial dependency.